Biosorption of Zn (II) Metal Ion by Ca-Alginate Immobilized Durian (Durio Zibethinus) Seed - Lestari, Intan (Journal of Chemical Natural Resources, 2019)
Heavy metal biosorption by alginate immobilized durian seed has been done. The immobilization of durian seed powder to Ca-alginate was able to improve biomass adsorption process, increase uptake capacity, ease separation from solution, generate and repeat biosorbent. In this experiment the effect of pH, contact time, concentration and temperature on the uptake capacity of metal ions Zn(II) in solution were studied. Biosorption was done batch methods and result was studied Langmuir and Freundlich adsorption isotherm. The adsorption of heavy metal was optimum in pH 5 with 75 mins contact time and Zn(II) ion under the concentration of 250-300 mg/l. The adsorption isotherm data was characterized using Langmuir and Freundlich equation. The equilibrium biosorption isotherm showed that alginate immobilized durian seed process has high affinities with adsorption capacities of 25.05 mg/g. All results showed that alginate immobilized durian seed is an alternative low cost biosorbent for heavy metal ion removal from aqueous solution